Prolactin and fMRI response to SKF38393 in the baboon - Miller, Brad D.; Marks, Lauren A.; Koller, Jonathan; Newman, Blake J.; Bretthorst, G. Larry; Black, Kevin J (PeerJ PrePrints, 2013)
Background: This study’s goal was to provide dose-response data for a dopamine agonist in the baboon using standard methods (replicate measurements at each dose, across a range of doses), as a standard against which to subsequently validate a novel pharmacological MRI (phMRI) method. Dependent variables were functional MRI (fMRI) data from brain regions selected a priori, and systemic prolactin release. Necessary first steps included estimating the magnitude and time course of prolactin response to anesthesia alone and to various doses of agonist. These first steps (“time course studies”) were performed with three agonists, and the results were used to select promising agonists and to guide design details for the single-dose studies needed to generate dose-response curves. Methods: We studied 6 male baboons (Papio anubis) under low-dose isoflurane anesthesia after i.m. ketamine. Time course studies charted the changes in plasma prolactin levels over time after anesthesia alone or after an intravenous (i.v.) dose of the dopamine D1-like agonists SKF82958 and SKF38393 or the D2-like agonist pramipexole. In the single-dose dopamine agonist studies, one dose of SKF38393 (ranging from 0.0928 – 9.28 mg/kg, N=5 animals) or pramipexole (0.00928 – 0.2 mg/kg, N=1) was given i.v. during a 40-minute blood oxygen level dependent (BOLD) fMRI session, to determine BOLD and plasma prolactin responses to different drug concentrations. BOLD response was quantified as the area under the time-signal curve for the first 15 minutes after the start of the drug infusion, compared to the linearly predicted signal from the baseline data before drug. The ED50(estimated dose that produces 50% of the maximal possible response to drug) for SKF38393 was calculated for the serum prolactin response and for phMRI responses in hypothalamus, pituitary, striatum and midbrain. Results: Prolactin rose 2.4- to 12-fold with anesthesia alone, peaking around 50-90 minutes after ketamine administration and gradually tapering off but still remaining higher than baseline on isoflurane 3-5 hours after ketamine. Baseline prolactin level increased with age. SKF82958 0.1mg/kg i.v. produced no noticeable change in plasma prolactin concentration. SKF38393 produced a substantial increase in prolactin release that peaked at around 20-30 minutes and declined to pre-drug levels in about an hour. Pramipexole quickly reduced prolactin levels below baseline, reaching a nadir 2-3 hours after infusion. SKF38393 produced clear, dose-responsive BOLD signal changes, and across the four regions, ED50 was estimated at 1.6-7.7mg/kg. Conclusions: In the baboon, the dopamine D1receptor agonist SKF38393 produces clear plasma prolactin and phMRI dose-response curves. Variability in age and a modest sample size limit the precision of the conclusions.
Keywords: pramipexole; SKF38393; dopamine D1 receptor agonists; ketamine; isoflurane; fMRI; Papio anubis; pharmacological fMRI; prolactin; SKF82958